2006
DOI: 10.1038/sj.jes.7500470
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of personal and indoor PM2.5 and absorbance among elderly subjects with coronary heart disease

Abstract: Epidemiological studies have established an association between outdoor levels of fine particles (PM 2.5 ) and cardiovascular health. However, there is little information on the determinants of PM 2.5 exposures among persons with cardiovascular disease, a potentially susceptible population group. Daily outdoor, indoor and personal PM 2.5 and absorbance (proxy for elemental carbon) concentrations were measured among elderly subjects with cardiovascular disease in Amsterdam, the Netherlands, and Helsinki, Finlan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
45
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 32 publications
9
45
3
Order By: Relevance
“…Our finding that the exposure variability for most particulate air pollutants was dominated by the within-person variance component is in agreement with previous studies that reported between-person and within-person variance components for environmental exposures to PM 2.5 , BS, or other air pollutants (Lee et al, 2004;Rappaport and Kupper, 2004;Egeghy et al, 2005;Lin et al, 2005;Sorensen et al, 2005;Lanki et al, 2007;Sarnat et al, 2009). Studies of particulate exposures in occupational settings have also reported larger within-person than between-person variance components (e.g., Kromhout et al, 1993;Symanski et al, 2006;Hagstrom et al, 2008).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Our finding that the exposure variability for most particulate air pollutants was dominated by the within-person variance component is in agreement with previous studies that reported between-person and within-person variance components for environmental exposures to PM 2.5 , BS, or other air pollutants (Lee et al, 2004;Rappaport and Kupper, 2004;Egeghy et al, 2005;Lin et al, 2005;Sorensen et al, 2005;Lanki et al, 2007;Sarnat et al, 2009). Studies of particulate exposures in occupational settings have also reported larger within-person than between-person variance components (e.g., Kromhout et al, 1993;Symanski et al, 2006;Hagstrom et al, 2008).…”
Section: Discussionsupporting
confidence: 82%
“…The median personal exposure to PM 2.5 in this study was comparable to levels reported from Boston , Seattle (Liu et al, 2003), and from Helsinki (Janssen et al, 2005;Lanki et al, 2007), but lower than levels reported from Minneapolis (Adgate et al, 2002), Toronto (Kim et al, 2005), Copenhagen (Sorensen et al, 2005), Vancouver (Ebelt et al, 2000), and Boston (Rojas-Bracho et al, 2004). Personal exposure to BS was lower than in Copenhagen (Sorensen et al, 2005), Helsinki, and Amsterdam (Janssen et al, 2005;Lanki et al, 2007).…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations